2021
DOI: 10.3390/foods10112838
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fresh Palm Fruit Sterilization in the Production of Carotenoid-Rich Virgin Palm Oil

Abstract: Palm oil is known to be rich in carotenoids and other phytonutrients. However, the carotenoids and phytonutrients degrade due to high heat sterilization of oil palm fruits. The present study was conducted to produce carotenoid-rich virgin palm oil (VPO) using cold-press extraction. Herein, the influence of sterilization of oil palm fresh fruits in the production of cold-pressed VPO was determined with varying sterilization temperatures, times, and amounts of palm fruits in sterilization. The experimental steri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A study by Mat Hassan et al reported that optimal heating condition was 62 °C for 90 min, producing 27.94% mild-heat pressed CPO with a minimal FFA content of 1.32%. 22 The study also demonstrated that mild-heat pressed CPO contains 48% more carotene than CPO from conventional milling. To learn more about the nutritional characteristics of mild-heat pressed CPO, the present study further explored other phytonutrients and antioxidants preserved during the mild thermal processing.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…A study by Mat Hassan et al reported that optimal heating condition was 62 °C for 90 min, producing 27.94% mild-heat pressed CPO with a minimal FFA content of 1.32%. 22 The study also demonstrated that mild-heat pressed CPO contains 48% more carotene than CPO from conventional milling. To learn more about the nutritional characteristics of mild-heat pressed CPO, the present study further explored other phytonutrients and antioxidants preserved during the mild thermal processing.…”
Section: Introductionmentioning
confidence: 79%
“…Mild-heat pressed CPO was produced as described by Mat Hassan et al . at a pilot-scale oil pressing facility, which included a benchtop autoclave (Astell Scientific Autoclave, UK), a digester (50 kg/batch), a twin-screw press (50 kg/h), and a benchtop centrifuge (Hettich Rotina 420, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations